Economic Development and Convergence In Sumatra Island, Indonesia : English - Arif Rahman; Monika Andrasari; Sirojuzilam Sirojuzilam (Fakultas Ekonomi dan Bisnis Islam UIN Alauddin Makassar, 2023)
The island of Sumatra, one of the largest contributors to the Indonesian economy, has experienced increased economic growth from time to time, but the acceleration of growth from each province has a different pace. This study aims to analyze the development and convergence of real per capita income that occurred on the island of Sumatra from 2011-2020, using panel data from 10 provinces in it. The novelty of this study incorporates Klassen's analysis as an effort to provide more concrete recommendations as well as the calculation of the half-life value per province which illustrates the convergence speed of each region. This can support the strength of the recommendation. We also divide the two observation periods, namely during normal conditions, and include 2020 as the year the economic shock occurred to compare changes in the convergence rate. Klassen's typology of economic development on the island of Sumatra for the 2016-2020 period shows a shift in the Riau Island Province towards being depressed and Bangka Belitung in the lagging zone. Meanwhile, Aceh Province is getting closer to the potential zone line. The level of inequality from the average value of the Williamson index is classified as moderate and during the year of observation shows an increase in value indicating convergence. The Covid-19 pandemic has reduced inequality, But on the other hand, the pandemic has also caused a decrease in real income in all the provinces observed, which means that welfare has decreased. The half-time value of each province implies economic stagnation that will occur in depressed developed regions and opens up opportunities for underdeveloped regions to spur growth in their real per capita income. In measuring the convergence itself, there was a convergence of real income per capita on the island of Sumatra. In other words, the conditional convergence model has a relatively higher convergence speed than the absolute convergence model. As an implication of the study, efforts to equalize per capita income on the island of Sumatra can be accelerated by spurring economic growth, HDI, and the distribution of gross fixed capital in areas that are in quadrants 3 and 4. Policies in eradicating poverty are a booster in accelerating the convergence process.